Student-Centered Learning Approach from Ibn Khaldun's Perspective: A Philosophical Study of the Concept of Learning in Islamic Education - Nur Ali Subhan; Muhammad Nur Rizal; Nur Khamid Al Mi’roj; Muhammad Rifki (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This article aims to analyze the concept of the student centered approach using Ibnu Khaldun's philosophical analysis approach in the book Muqaddimah. This research uses a library research method using a qualitative descriptive approach. Data collection uses documentation methods with content analysis techniques to systematically analyze the content of messages and reveal hidden symbolic meanings in primary sources. The results of the research show that Ibn Khaldun's style of thinking about the student centered approach in the Muqaddimah book is strong with the understanding of humanism which is oriented towards glorifying and interpreting students as whole humans. Ibn Khaldun's humanism towards students can be seen from his view of students as thinking creatures, social creatures, having potential, requiring motivation, love, various methods, involvement and spiritual balance in the educational process. Ibn Khaldun's humanism in viewing students as the center of education is colored by idealism. Students as perfect beings in the learning center can reach the peak of perfection with the help of the educational environment. As spiritual beings, students will be able to develop all their potential by maintaining spiritual balance